Demanded competencies of specialists in human resource development in physical culture and sports organizations - Vorobyev S.A. ,; Tsareva A.V. ,; Breyder N.A. ,; Malinin A.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to analyze the demand for specialists with various qualifications in order to improve the effectiveness of organizations in the field of physical culture and sport in the Russian Federation. Methods and structure of the study. In 2024, the Saint-Petersburg Scientific-Research Institute for Physical Culture (SPbSRIFPC) conducted an online survey of specialists from state and municipal physical culture and sports organizations located in 82 constituent entities of the Russian Federation (n=2059) using specialized software. Results and conclusions. The article presents the priorities identified during the study regarding the demand for various groups of specialist competencies, and also examines the demand for specific competencies within the most significant groups. According to the survey results, the most sought-after competencies for the development of the human resources potential of organizations in the three-year perspective are the groups of competencies related to the organization and conduct of physical education and sports events, legal support for physical education and sports, IT technologies and digitalization processes in sport, as well as financial and economic planning.